Sodium bicarbonate supplementation improved MAOD but is not correlated with 200- and 400-m running performances: a double-blind, crossover, and placebo-controlled study - Brisola, Gabriel Motta Pinheiro [UNESP]; Miyagi, Willian Eiji [UNESP]; Silva, Henrique Santos da [UNESP]; Zagatto, Alessandro Moura [UNESP] (Canadian Science Publishing, 2015)
The aim of the study was to investigate the effects of acute supplementation of sodium bicarbonate (NaHCO3) on maximal accumulated oxygen deficit (MAOD) determined by a single supramaximal effort (MAODALT) in running and the correlation with 200- and 400-m running performances. Fifteen healthy men (age, 23 ± 4 years; maximal oxygen uptake, 50.6 ± 6.1 mL·kg(-1)·min(-1)) underwent a maximal incremental exercise test and 2 supramaximal efforts at 110% of the intensity associated with maximal oxygen uptake, which was carried out after ingesting either 0.3 g·kg(-1) body weight NaHCO3 or a placebo (dextrose) and completing 200- and 400-m performance tests. The study design was double-blind, crossover, and placebo-controlled. Significant differences were found between the NaHCO3 and placebo conditions for MAODALT (p = 0.01) and the qualitative inference for substantial changes showed a very likely positive effect (98%). The lactic anaerobic contribution in the NaHCO3 ingestion condition was significantly higher (p < 0.01) and showed a very likely positive effect (99% chance), similar to that verified for peak blood lactate concentration (p < 0.01). No difference was found for time until exhaustion (p = 0.19) or alactic anaerobic contribution (p = 0.81). No significant correlations were observed between MAODALT and 200- and 400-m running performance tests. Therefore, we can conclude that both MAODALT and the anaerobic lactic metabolism are modified after acute NaHCO3 ingestion, but it is not correlated with running performance.
Keywords: Anaerobic capacity; Bicarbonate de sodium; Blood lactate; Capacité anaérobie; Efforts supramaximaux; Ergogenic aid; Facteur ergogène; Lactate sanguin; Sodium bicarbonate; Supramaximal efforts